Anti-hla donor-specific antibodies are associated to infection and not to the engraftment rate in outpatient haploidentical hematopoietic cell transplantation - José C. Jaime-Pérez; María L. Ruiz-De la Cruz; Sandra I. Mendoza-Ibarra; Nidia K. Moncada-Saucedo; David Gomez-Almaguer (Permanyer, 2023)
Background: Recipients of a related haploidentical stem cell transplant (haplo-SCT) can have preformed antibodies to HLA donor's antigens. Objective: The aim of the study was to evaluate the engraftment rate and major clinical associations of anti-HLA donor-specific antibodies (DSA) at two mean fluorescence intensity (MFI) thresholds in recipients of an outpatient haplo-SCT. Methods: Seventy haplo-HCT recipients were analyzed. A virtual crossmatch was performed using the donor HLA typing and the recipient's anti-HLA DSA test results. Data for anti-HLA-A, -B, -C, and -DR were analyzed. Recipients with DSA ≥ 500 MFI were considered positive, and those with < 500 were considered negative; the same was adopted for MFI ≥ 1000. Results: Post-transplant infection was higher in recipients with DSA ≥ 500 MFI (84.6%, p = 0.041). First-year mortality was higher in DSA-positive patients ≥ 500 MFI, p = 0.004, and DSA ≥ 1000 MFI, p = 0.022, than in DSA-negative recipients. Graft failure in the first 100 days was not associated with DSA ≥ 500 or ≥ 1000 MFI. There was no difference in acute (a-GVHD) or chronic (c-GVHD) graft versus host disease between DSA-positive and negative patients. Conclusions: There was no association of anti-HLA DSA at MFI ≥ 500 and ≥ 1000 with graft failure, however, increased infection and 1st-year mortality were documented in related haplo-HCT at the MFI cutoffs studied.